INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) INTEGRATION IN THE TEACHING OF ENGLISH:A SYSTEMATIC REVIEW - Agus Rofi'i; Widia Siska; Nurfadillah Yunus; Yulian Purnama; Husna Imro'athush Sholihah (Adisam Publisher, 2024)
The use of information technology significantly enhances the study of the English language. Through easy access to learning resources, learning applications, multimedia-based learning, global communication and collaboration, e-assessment, and self-directed learning, ICT helps students acquire English knowledge and skills more effectively and happily. Appropriate and targeted use of ICT in English language learning can increase students' motivation, broaden their horizons, and prepare them to face challenges in an increasingly connected global world. This study aims to evaluate the effectiveness and impact of ICT integration in English language teaching through a systematic review of the literature. Data and information about the incorporation of ICT in English language instruction were gathered through a survey of the literature. It is crucial to incorporate technology into the teaching and learning process in order to promote digital literacy.